Smart garbage monitoring system - Amalia Witra, Jailani (2019)
One of the challenges to transform and make an Internet of Things (IoT) is in monitoring and managing of the environment. One of the challenges to the local authority is how to monitor the works of employee effective and efficiency in waste management. Waste product collection utilizes the IoT with the technology of sensors that will able to collect the data from a garbage bin. From the finding of this investigation, it can be concluding that through management of collecting data from the volunteer by stakeholders can enhance the visualization of intelligent smart waste management system. This documentation will purpose to the local authority the implementation of smart waste management to provide better services to the public towards smart city applications and improve and increase the city management.